A Randomized Open-Labeled Trial of Methotrexate as a Steroid-Sparing Agent for Patients With Generalized Myasthenia Gravis - Di, Li; Shen, Faxiu; Wen, Xinmei; Lu, Yan; Zhu, Wenjia; Wang, Min; Da, Yuwei (Frontiers in Immunology, 2022)
Background and purpose: Two clinical trials assessing the steroid-sparing effect of methotrexate (MTX) yielded conflicting results. Our objective was to investigate whether MTX would show steroid-sparing effect in the treatment of generalized myasthenia gravis (MG) patients who fitted Myasthenia Gravis Foundation of America (MGFA) Class II and Class III. Methods: We performed an 18-month prospective, randomized, open-labeled trial of prednisone combined with MTX 10 mg orally every week versus prednisone alone in 40 recently diagnosed MG patients of MGFA Class II and Class III between July 2014 and July 2018. The primary endpoint was the prednisone area under the dose-time curve (AUDTC) from months 3 to 18. Secondary endpoints included changes of the Quantitative Myasthenia Gravis Score (QMG), the Myasthenia Gravis Activity of Daily Living Score (MG-ADL), initial time of prednisone reduction, the median prednisone daily dose in each month, adverse events and treatment failures in each group. Results: Forty participants were included, among those, 5 individuals withdrew. A total of 35 participants completed 18 months of follow-up (18 in prednisone+MTX, 17 in prednisone group). Combined use of MTX reduced the month 3–18 prednisone AUDTC (prednisone+MTX 5663.44 ± 1678.08 mg，prednisone 6683.94 ± 678.08 mg, p=0.03, 95% confidence interval -1916.01 to -124.98). Initial time of prednisone reduction were 4.34±1.44 months in prednisone+MTX group and 5.56±2.05 months in prednisone group (p=0.04, 95% CI -2.41 to -0.03). The median daily prednisone dose was significantly lower in prednisone+MTX group at month 6 and month 9-18. No significant differences were found in QMG and MG-ADL scores between the two groups. No serious drug-related adverse events were observed in both groups. Conclusions: This study provides evidence that MTX has the steroid-sparing ability in generalized MG patients of MGFA Class II and Class III. Clinical Trial Registration: http://www.chictr.org.cn/showproj.aspx?proj=10563 identifier ChiCTR-IPR-15006081.